Development of an Efficient Transient Gene Expression Assay Based on Tobacco ((Nicotiana tabacum var. Xanthi) Male Gametophytes - Akhond, M. A. Y.; Machray, G. C. (Plant Tissue Culture and Biotechnology, 2010)
Optimization of direct DNA delivery into tobacco ((Nicotiana tabacum var. Xanthi) male gametophytes was devised together with development of an efficient transient expression system to study gene expression under controlled conditions. Use of a GFP gene driven by strong promoter and enhancer sequences allowed an efficient non-lethal transient gene expression assay with an overall transient gene expression frequency of > 4% for uninucleate microspores and between 10 and 20% for binucleate pollen. The technique demonstrated its suitability for analysis of developmental stage-specific gene expression. The assay allowed observation of real-time transgene expression during microspore maturation proving useful for in vitro pollen selection. We have also used this protocol to determine the recombination potential of tobacco male gametic cells by assessing the frequency of extra-chromosomal homologous recombination events after co-delivery of two loss-of-function GFP genes. No increase of extrachromosomal recombination was observed in assays for transient transformation.Key words: Biolistic, GFP, Microspore, Tobacco, Nicotiana tabacum, TransformationD.O.I. 10.3329/ptcb.v19i1.4078Plant Tissue Cult. & Biotech. 19(1): 9-23, 2009 (June)